STRATEGIES FOR DEVELOPING SCIENTIFIC SKILLS AND ATTITUDES IN PHYSICS EDUCATION AMONG SECONDARY SCHOOL STUDENTS IN EBONYI STATE, SOUTHEAST NIGERIA - Ali, Peter A. (International Journal of Research Science and Management, 2020)
This study was carried out to identify the strategies for the development of scientific skills and attitudes in physics education among secondary students in Ebonyi state, southeast Nigeria. One research question was developed in line with the purpose of the study. One null hypothesis was formulated and tested at 0.05 level of significance. The study adopted descriptive survey design. The population of the study is 2370 students and 87 teachers, and the sample comprised 600 students and 25 teachers of physics from the area of study. This sample was drawn using multi-stage sampling technique. An–11 item instrument termed "Science Skills and Attitudes in Physics Questionnaire" (SSAPQ) was used by the researcher for data collection. The instrument was first validated by experts and reliability was determined using Cronbach Alpha Statistics and the reliability got was 0.82. The administration and retrieval of instrument were through direct contact and use of research assistants with the respondents. Data collected were analysed using mean and standard deviation for the research question while ttest statistics were used for testing the null hypothesis. The findings of the study revealed that 9 out of 11 items presented are the strategies for the development of scientific skills and attitudes in physics education among secondary students in Ebonyi state, southeast Nigeria. Findings on the hypothesis tested revealed that there was no significant difference in the mean responses of students and teachers of physics from Ebonyi state on the items presented. Holistic reformation of the physics curriculum to incorporate the strategies, appropriate training of teachers to ensure quality transmission of scientific knowledge, skills and attitudes and provision of needed laboratory facilities, books and other learning materials by the relevant stakeholders were recommended.